Facterra - Faghihi, Kevin; Hellgård, Adam; Karlsson, Linus; Adamsson, Simon; Wiman Ohlson, Noel; Otterlind, Ludvig (My University, 2025)
A massive amount of waste is generated globally, and the circular economy offers a promising approach to reduce it by reusing resources and minimizing environmental impact. Raising public awareness is a key step toward supporting this transition. One potential method for raising awareness is through video games. This project aimed to design and develop Facterra, a 2D factory simulation game that is both fun and educational, with a focus on environmental impact and the circular economy. To evaluate whether the game achieved its goals, playtesting was conducted where players experienced the game and answered a combination of surveys and interview questions. The results indicated that Facterra successfully engaged players and conveyed its intended message, further showing that games indeed can be used to raise awareness. However, feedback also highlighted areas for improvement, particularly in terms of polish, depth, and clarity of educational elements.
Keywords: Serious Games, Game-Based Learning, Production Chains Simulation, Environmental Awareness, Circular Economy